Electronic aluminum foil and method of making the same and capacitor

CN122907512APending Publication Date: 2026-10-13XINJIANG JOINWORLD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611237078.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

其中,箔轧工序为电子铝箔成型的核心工序,轧制过程中会难以避免残留有机轧制油、微细铝粉等杂质,若杂质无法有效去除,最终造成铝箔表面氧化膜厚度不均匀,影响产品的比电容

Benefits of technology

[0030]上述电子铝箔的制备工艺使铝箔表面更加均匀,更有利于后续的腐蚀,经电化学腐蚀后,在折弯基本相同的条件下,容量更高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907512A_ABST
    Figure CN122907512A_ABST
Patent Text Reader

Abstract

The application relates to an electronic aluminum foil and a preparation method and a capacitor thereof. The preparation method comprises the following steps: performing plasma cleaning on an aluminum foil rolling product in a working gas, the working gas comprising the following components in percentage by volume: Ar 26%-30%, N2 68%-73.5% and O2 0.5%-2% under the condition of a power density of 4 W / cm 2 7 W / cm 2 ; and sequentially performing pulse treatment, shearing treatment and annealing treatment on the aluminum foil after the plasma cleaning to prepare the electronic aluminum foil. The electronic aluminum foil prepared through the above process has the advantages of high surface cleanliness, good oxidation film uniformity, good corrosion hole uniformity and high specific capacity, and is more suitable for capacitor use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of aluminum foil processing technology, and in particular to electronic aluminum foil, its preparation method, and capacitors. Background Technology

[0002] Anode aluminum foil is a key material in the production of electrolytic capacitors. The most important factor determining the high specific capacitance after the anode aluminum foil is etched is the surface quality of the aluminum foil. Problems with foil adhesion can lead to defects in the aluminum surface, thus affecting the improvement of specific capacitance.

[0003] Currently, the production process of electronic aluminum foil includes: casting → homogenization → hot rolling → cold rolling → foil rolling → intermediate annealing → finished foil → cleaning → slitting → finished product annealing → rewinding. Among these, the foil rolling process is the core process for forming electronic aluminum foil. During rolling, it is difficult to avoid residual organic rolling oil, fine aluminum powder, and other impurities. If these impurities are not effectively removed, the oxide film thickness on the aluminum foil surface will be uneven, affecting the specific capacitance of the product. Furthermore, in the high-temperature environment of subsequent finished product annealing, residual rolling oil is prone to high-temperature decomposition, forming carbon stains and color defects on the aluminum foil surface. It also easily causes foil layer adhesion and coking of production equipment, which not only seriously affects the subsequent rewinding process but also damages the flatness and uniformity of the aluminum foil surface, leading to uneven corrosion, localized over-corrosion, or under-corrosion during subsequent etching processes, significantly reducing the corrosion uniformity and electrostatic capacitance of the electronic aluminum foil.

[0004] In traditional cleaning processes, oil cleaning primarily uses light white oil as a solvent. However, white oil cleaning has limited ability to remove fine aluminum powder, easily forming "oil-encapsulated powder" composite stains, affecting the uniformity of subsequent corrosion. Although light white oil is relatively environmentally friendly, its recycling cost is high. Alkaline washing, water washing, or acid washing processes result in large wastewater discharges, high environmental treatment costs, high energy consumption requiring multi-stage heating and drying (accounting for more than 15% of the total production line energy consumption), and a tendency to introduce ionic residues (such as sodium). + Cl - Issues such as oil washing, alkali washing, water washing, or acid washing are all present. Regardless of whether the aluminum foil rolls are washed with oil, alkali, water, or acid, they all need to be transported back to the slitting process after cleaning to cut the large rolls into smaller rolls. However, multiple transfers can easily cause secondary damage to the aluminum foil rolls due to collisions, further increasing the risk of surface defects and reducing the yield and production stability of electronic aluminum foil.

[0005] Therefore, traditional technologies still need improvement. Summary of the Invention

[0006] Therefore, it is necessary to provide an electronic aluminum foil with high surface cleanliness, good oxide film uniformity, good corrosion pore uniformity, and high specific capacitance, as well as its preparation method and capacitor.

[0007] This application is achieved through the following technical solution:

[0008] One aspect of this application provides a method for preparing electronic aluminum foil, comprising the following steps:

[0009] In the working gas, the power density is 4 W / cm³ 2 ~7 W / cm 2 Under these conditions, aluminum foil rolls are subjected to plasma cleaning. The working gas, by volume percentage, comprises the following components: Ar2 26%~30%, N2 68%~73.5%, and O2 0.5%~2%; and

[0010] The aluminum foil after plasma cleaning is annealed to prepare electronic aluminum foil.

[0011] The above-mentioned method for preparing electronic aluminum foil first involves plasma cleaning of the rolled aluminum foil. The composition and ratio of the working gas used in the plasma cleaning are controlled. Ar, as an inert gas, provides high-energy particle bombardment to remove loose aluminum powder and surface oxide particles from the foil surface. N2, as the base carrier gas, continuously forms an insulating gas curtain on the aluminum foil surface, inhibiting secondary oxidation during the cleaning process, stabilizing the plasma jet morphology, and lowering the cleaning temperature. O2 participates in the plasma chemical oxidation reaction, breaking the long organic chains of the rolling oil and thoroughly decomposing organic oil stains on the foil surface. The synergistic effect of each component effectively removes residual rolling oil, fine aluminum powder, and other impurities. Furthermore, controlling the plasma power density enhances the decontamination effect. Finally, the plasma-cleaned aluminum foil is annealed to prepare the electronic aluminum foil. This process results in electronic aluminum foil with high surface cleanliness, good oxide film uniformity, good corrosion pore uniformity, and high specific capacitance, making it more suitable for capacitor applications.

[0012] In some embodiments, the working gas comprises, by volume percentage, the following components:

[0013] Ar 28%~30%, N2 68%~70.8% and O2 1.2%~2%.

[0014] In some embodiments, the method for preparing the electronic aluminum foil satisfies one or more of the following conditions:

[0015] (1) The thickness of the aluminum foil rolled product is 80μm~130μm;

[0016] (2) The dew point of the working gas source is less than or equal to -25℃;

[0017] (3) The plasma cleaning time is 4s~12s;

[0018] (4) The annealing temperature is 250℃~580℃ and the time is 25h~38h.

[0019] In some embodiments, during the plasma cleaning process of the aluminum foil rolls, the moving speed of the aluminum foil rolls is less than or equal to 150 m / min, and the composition and power density of the working gas are adjusted in real time as the moving speed of the aluminum foil rolls increases from 0 to 150 m / min.

[0020] In some embodiments, as the moving speed of the aluminum foil roll increases from 0 to 130 m / min, the power density increases from 4 W / cm². 2 Adjusted to 6.5W / cm 2 The volume ratio of Ar, N2 and O2 was adjusted from 26:73.5:0.5 to 29:69.5:1.5.

[0021] In some embodiments, the method for preparing the electronic aluminum foil satisfies one or more of the following conditions:

[0022] (1) Before the step of annealing the aluminum foil after plasma cleaning, the aluminum foil after plasma cleaning is further subjected to pulse treatment and shearing treatment in sequence.

[0023] (2) The process of plasma cleaning of aluminum foil rolled products also includes negative pressure suction of aluminum foil to remove the detached aluminum powder particles.

[0024] In some embodiments, the method for preparing the electronic aluminum foil satisfies one or more of the following conditions:

[0025] (1) The frequency of pulse processing is 10Hz~68Hz;

[0026] (2) The pressure of negative pressure suction is -80 Pa to -120 Pa.

[0027] In some embodiments, prior to the plasma cleaning step of the aluminum foil roll, a surface pretreatment step is included to remove free impurities from the foil surface.

[0028] In another aspect, this application provides an electronic aluminum foil, which is prepared using the above-described method for preparing electronic aluminum foil.

[0029] Another aspect of this application provides a capacitor, including an anode, a cathode, a diaphragm, and an electrolyte, wherein the anode is made from an electronic aluminum foil prepared by the method described above or from the electronic aluminum foil described above.

[0030] The above-mentioned preparation process of electronic aluminum foil makes the aluminum foil surface more uniform, which is more conducive to subsequent corrosion. After electrochemical corrosion, the capacity is higher under basically the same bending conditions. Attached Figure Description

[0031] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0032] Figure 1 This is a SEM image of the surface morphology of the electronic aluminum foil prepared in Example 1 of this application after etching.

[0033] Figure 2 This is a SEM image of the surface morphology of the electronic aluminum foil obtained in Example 2 of this application after etching.

[0034] Figure 3 This is a SEM image of the surface morphology of the electronic aluminum foil obtained in Example 3 of this application after etching.

[0035] Figure 4 The SEM image shows the surface morphology of the electronic aluminum foil prepared in Comparative Example 1 of this application after etching.

[0036] Figure 5 The SEM image shows the surface morphology of the electronic aluminum foil prepared in Comparative Example 2 of this application after etching.

[0037] Figure 6 This is a SEM image of the surface morphology of the electronic aluminum foil prepared in Comparative Example 3 of this application after etching.

[0038] Figure 7 This is a SEM cross-sectional morphology image of the electronic aluminum foil prepared in Example 1 of this application after etching.

[0039] Figure 8 This is a SEM cross-sectional morphology image of the electronic aluminum foil obtained in Example 2 of this application after etching.

[0040] Figure 9 This is a SEM cross-sectional morphology image of the electronic aluminum foil prepared in Example 3 of this application after etching.

[0041] Figure 10 This is a SEM image of the cross-sectional morphology of the electronic aluminum foil prepared in Comparative Example 1 of this application after etching.

[0042] Figure 11 This is a SEM image of the cross-sectional morphology of the electronic aluminum foil prepared in Comparative Example 2 of this application after etching.

[0043] Figure 12This is a SEM image of the cross-sectional morphology of the electronic aluminum foil prepared in Comparative Example 3 of this application after etching. Detailed Implementation

[0044] Reference will now be made to detailed embodiments of this application, one or more of which are described below. Each example is provided for explanation and not for limitation of this application. In fact, it will be apparent to those skilled in the art that various modifications and variations can be made to this application without departing from its scope or spirit. For example, features described or illustrated as part of one embodiment may be used in another embodiment to produce further embodiments.

[0045] Therefore, this application is intended to cover such modifications and variations falling within the scope of the appended claims and their equivalents. Other objects, features, and aspects of this application are disclosed in or will be apparent from the following detailed description. It will be understood by those skilled in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of this application.

[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0047] The terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element preceded by the phrase “comprising one…” does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. The indefinite articles “a” and “an” preceding an element or component in this application are not restrictive in terms of the quantity (i.e., the number of times) of the element or component. Therefore, “an” or “a” should be interpreted as including one or at least one, and singular elements or components also include plural forms, unless the quantity clearly refers only to the singular. “A plurality” means at least two, such as two, three, etc., unless otherwise expressly specified.

[0048] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the weights mentioned in the embodiments of this application can be well-known units of mass in the chemical industry, such as μg, mg, g, and kg.

[0049] Unless otherwise shown or indicated in the operational embodiments, all figures used to represent the amounts, physicochemical properties, etc., of ingredients in the specification and claims are to be understood to be adjusted by the term "about" in all cases. For example, therefore, unless stated to the contrary, the numerical parameters listed in the foregoing specification and appended claims are approximations, and those skilled in the art can appropriately modify these approximations to obtain the desired characteristics by utilizing the teachings disclosed herein. The use of numerical ranges indicated by endpoints includes all numbers within that range and any range within that range; for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4, and 5, etc.

[0050] One embodiment of this application provides a method for preparing electronic aluminum foil, including the following steps S100 to S200.

[0051] Step S100: In the working gas, with a power density of 4 W / cm³ 2 ~7 W / cm 2 Under these conditions, aluminum foil rolled products are subjected to plasma cleaning. The composition of the working gas, by volume percentage, includes the following components: Ar 26%~30%, N 268%~73.5% and O2 0.5%~2%.

[0052] Step S200: Anneal the plasma-cleaned aluminum foil to prepare electronic aluminum foil.

[0053] The above-mentioned method for preparing electronic aluminum foil first involves plasma cleaning of the rolled aluminum foil. The composition and ratio of the working gas used in the plasma cleaning are controlled. Ar, as an inert gas, provides high-energy particle bombardment to remove loose aluminum powder and surface oxide particles from the foil surface. N2, as the base carrier gas, continuously forms an insulating gas curtain on the aluminum foil surface, inhibiting secondary oxidation during the cleaning process, stabilizing the plasma jet morphology, and lowering the cleaning temperature. O2 participates in the plasma chemical oxidation reaction, breaking the long organic chains of the rolling oil and thoroughly decomposing organic oil stains on the foil surface. The synergistic effect of each component effectively removes residual rolling oil, fine aluminum powder, and other impurities. Furthermore, controlling the plasma power density enhances the decontamination effect. Finally, the plasma-cleaned aluminum foil is annealed to prepare the electronic aluminum foil. This process results in electronic aluminum foil with high surface cleanliness, good oxide film uniformity, good corrosion pore uniformity, and high specific capacitance, making it more suitable for capacitor applications.

[0054] It should be noted that the power density values ​​mentioned above range from 4 W / cm². 2 ~7 W / cm 2 ", then 4 W / cm 2 ~7W / cm 2 The minimum and maximum values ​​within the range, and every value between these minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 4.0 W / cm², 4.1 W / cm². 2 4.2 W / cm 2 4.3 W / cm 2 4.4W / cm 2 4.5 W / cm 2 4.6 W / cm 2 4.7 W / cm 2 4.8 W / cm 2 4.9 W / cm 2 5.0 W / cm 2 5.1 W / cm 2 5.2W / cm 2 5.3 W / cm 2 5.4 W / cm 2 5.5 W / cm 2 5.6 W / cm 2 5.7 W / cm 2 5.8 W / cm 2 5.9 W / cm 2 6.0W / cm 2 6.1 W / cm 2 6.2 W / cm 26.3 W / cm 2 6.4 W / cm 2 6.5 W / cm 2 6.6 W / cm 2 6.7 W / cm 2 6.8W / cm 2 6.9 W / cm 2 Or 7.0 W / cm 2 Or a range consisting of any two of these values, for example, including: 4 W / cm 2 ~6 W / cm 2 .

[0055] The value range of Ar mentioned above is "26%~30%", which means it can take the minimum and maximum value of the range of 26%~30%, as well as every value between the minimum and maximum value. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 26.0%, 26.2%, 26.4%, 26.6%, 26.8%, 27.0%, 27.2%, 27.4%, 27.6%, 27.8%, 28.0%, 28.2%, 28.4%, 28.6%, 28.8%, 29.0%, 29.2%, 29.4%, 29.6%, 29.8% or 30.0%, or a range consisting of any two of these values. For example, it includes: 26%~29%.

[0056] The value range of N2 mentioned above is "68%~73.5%", which means it can take the minimum and maximum value of the range of 68%~73.5%, as well as every value between the minimum and maximum value. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 68.0%, 68.2%, 68.4%, 68.6%, 68.8%, 69.0%, 69.2%, 69.4%, 69.6%, 69.8%, 70.0%, 70.2%, 70.4%, 70.6%, 70.8%, 71.0%, 71.2%, 71.4%, 71.6%, 71.8%, 72.0%, 72.2%, 72.4%, 72.6%, 72.8%, 73.0%, 73.2%, 73.4% or 73.5%, or a range consisting of any two of these values. For example, it includes: 68%~72%.

[0057] The value range of O2 mentioned above is "0.5%~2%", which means it can take the minimum and maximum value of the range of 0.5%~2%, as well as every value between the minimum and maximum value. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9% or 2%, or any range of any two of these values. For example, it includes: 0.5%~1.5%.

[0058] In some embodiments, the working gas comprises, by volume percentage, the following components:

[0059] Ar 28%~30%, N2 68%~70.8% and O2 1.2%~2%.

[0060] It is understandable that by controlling the composition of the working gas within the above range, the surface cleanliness, oxide film uniformity, corrosion pore uniformity, and specific volume of the electronic aluminum foil produced are superior.

[0061] In some embodiments, the thickness of the rolled aluminum foil is 80μm to 130μm. For example, the above thickness can be 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, or 130μm. In some examples, it can be any two of these point values ​​as end values ​​within the range. The same applies below.

[0062] In some embodiments, the dew point of the working gas source is less than or equal to -25°C.

[0063] In some embodiments, the dew point of the working gas source is -45°C to -25°C.

[0064] In some embodiments, the plasma cleaning time is 4s to 12s.

[0065] In some embodiments, the annealing temperature is 250°C to 580°C and the time is 25h to 38h. For example, the annealing temperature can be 250°C, 270°C, 290°C, 310°C, 330°C, 350°C, 370°C, 390°C, 410°C, 430°C, 450°C, 470°C, 490°C, 510°C, 530°C, 550°C, 570°C, or 580°C.

[0066] In some embodiments, during the plasma cleaning process of the aluminum foil rolls, the moving speed of the aluminum foil rolls is less than or equal to 150 m / min, and the composition and power density of the working gas are adjusted in real time as the moving speed of the aluminum foil rolls increases from 0 to 150 m / min.

[0067] Under the aforementioned power and velocity conditions, the fresh aluminum surface active sites generated by high-energy ion bombardment compete with oxygen-containing free radicals in the gas phase for adsorption within milliseconds. This occurs precisely at the critical turning point between "complete removal of contaminants" and "the initiation of nucleation of dense barrier Al2O3." The resulting layer is an ultrathin transition oxide layer rich in hydroxyl groups (-OH) and less than 5 nm thick, rather than the thick and disordered natural oxide film commonly found in traditional cleaning processes.

[0068] In some embodiments, as the moving speed of the aluminum foil roll increases from 0 to 130 m / min, the power density increases from 4 W / cm². 2 Adjusted to 6.5W / cm 2 The volume ratio of Ar, N2 and O2 was adjusted from 26:73.5:0.5 to 29:69.5:1.5.

[0069] In some embodiments, during the plasma cleaning process of the aluminum foil roll, the moving speed of the aluminum foil roll is 0 ~ 150 m / min.

[0070] In some embodiments, during the plasma cleaning process of the aluminum foil roll, the moving speed of the aluminum foil roll is 5 m / min to 150 m / min.

[0071] In some embodiments, during the plasma cleaning process of the aluminum foil roll, the moving speed of the aluminum foil roll is 130 m / min to 150 m / min.

[0072] In some embodiments, the movement speed of the aluminum foil roll is adjusted by uniform speed processing.

[0073] In some embodiments, the acceleration time of the aluminum foil roll is less than or equal to 2 minutes.

[0074] In some embodiments, the working gas adjustment rate is processed at a constant rate.

[0075] In some embodiments, the adjustment rate of the power density is processed at a constant rate.

[0076] In some embodiments, as the moving speed of the aluminum foil roll decreases from 130 m / min to 0, the power density decreases from 6.5 W / cm². 2 Adjust to 4W / cm 2 The volume ratio of Ar, N2 and O2 was adjusted from 29:69.5:1.5 to 26:73.5:0.5.

[0077] In some embodiments, before the step of annealing the plasma-cleaned aluminum foil, the steps of sequentially pulse-processing and shearing the plasma-cleaned aluminum foil are included.

[0078] In some embodiments, the frequency of the pulse processing described above is 10Hz to 68Hz. For example, the frequency can be 10Hz, 11Hz, 12Hz, 13Hz, 14Hz, 15Hz, 16Hz, 17Hz, 18Hz, 19Hz, 20Hz, 21Hz, 22Hz, 24Hz, 26Hz, 28Hz, 30Hz, 32Hz, 34Hz, 36Hz, 38Hz, 40Hz, 42Hz, 44Hz, 46Hz, 48Hz, 50Hz, 52Hz, 54Hz, 56Hz, 58Hz, 60Hz, 62Hz, 64Hz, 66Hz, or 68Hz.

[0079] It is understandable that the above pulse treatment can prevent the detached aluminum powder from being re-adsorbed due to static electricity.

[0080] In some embodiments, the process of plasma cleaning the aluminum foil rolls also includes negative pressure suction of the aluminum foil to remove the detached aluminum powder particles.

[0081] In some embodiments, the negative pressure suction pressure is -80 Pa to -120 Pa. For example, the pressure can be -120 Pa, -118 Pa, -116 Pa, -114 Pa, -112 Pa, -110 Pa, -108 Pa, -106 Pa, -104 Pa, -102 Pa, -100 Pa, -98 Pa, -96 Pa, -94 Pa, -92 Pa, -90 Pa, -88 Pa, -86 Pa, -84 Pa, -82 Pa, or -80 Pa.

[0082] Understandably, the negative pressure suction removes the detached aluminum powder particles in real time to prevent secondary sedimentation, while forced convection lowers the temperature of the aluminum foil after cleaning.

[0083] In some embodiments, prior to the plasma cleaning step of the aluminum foil roll, a surface pretreatment step is included to remove free impurities from the foil surface.

[0084] Another embodiment of this application provides an electronic aluminum foil, which is prepared using the above-described method for preparing electronic aluminum foil.

[0085] The aforementioned electronic aluminum foil features high surface cleanliness, good oxide film uniformity, good corrosion pore uniformity, and high specific volume.

[0086] Another embodiment of this application provides a capacitor including an anode, a cathode, a diaphragm, and an electrolyte, wherein the anode is made using the electronic aluminum foil prepared by the above-described method or by the above-described electronic aluminum foil.

[0087] The aforementioned preparation process for electronic aluminum foil results in a more uniform aluminum foil surface, which is more conducive to subsequent corrosion. After electrochemical corrosion, the foil exhibits higher capacity under essentially the same bending conditions. Furthermore, the process is simple to operate, low in cost, uses common reagents and equipment, requires minimal technical expertise from operators, and is suitable for large-scale industrial production.

[0088] In some embodiments, at least one side of the anode is made of the aforementioned electronic aluminum foil.

[0089] In some embodiments, a diaphragm is disposed between the anode and the cathode, and an electrolyte is disposed between the anode and the cathode and wets the diaphragm.

[0090] To better illustrate this application, the following description, in conjunction with specific embodiments, further explains its content. The following are specific embodiments.

[0091] Example 1

[0092] (1) After the high-pressure foil of 0.125mm is rolled, the aluminum foil product is continuously fed from the unwinding device into the sealed processing chamber. Clean and dry compressed nitrogen (0.3 MPa) is used to blow the foil surface through the transverse air knife at a distance of 5mm from the foil surface to remove the free rolling oil and loosely attached aluminum powder. An air curtain is set between the blowing area and the plasma chamber to prevent oil mist from entering other working areas.

[0093] (2) Select the aluminum foil roll obtained in step (1) above and transfer it to the cleaning process. The aluminum foil roll is cleaned according to the plasma cleaning method of this embodiment. An atmospheric pressure jet plasma generator is used, and the cleaning parameters are set as follows: plasma power density is 5.8 W / cm². 2 The processing time is 6 seconds. The working gas is a ternary mixture of Ar / N2 / O2 (specifically, the volume ratio is 28% Ar, 70.8% N2, and 1.2% O2), with a dew point of -40℃ and an aluminum foil moving speed of 100 m / min. A micro-negative pressure suction port (relative pressure of -100 Pa) is set below the plasma treatment zone to remove the detached aluminum powder particles in real time, preventing secondary sedimentation, while forced convection reduces the temperature of the aluminum foil after cleaning.

[0094] (3) A pulsed AC ion bar electrostatic elimination device is installed at the outlet of the plasma dry cleaning unit; the distance between the ion bar and the aluminum foil surface is controlled at 80 mm, the ion pulse output frequency is 47 Hz, the output frequency is linked with the production line speed, the ion balance voltage is maintained within ≤30V, and 0.2MPa clean dry nitrogen is used for transverse purging; after electrostatic neutralization, the residual electrostatic voltage on the aluminum foil surface is ≤100V, eliminating the secondary adsorption of fallen aluminum powder due to electrostatics. The treated aluminum foil immediately enters the disc shearing mechanism, which cuts it according to the set width, and cuts the aluminum foil roll into sheared rolls with a width of 500 mm.

[0095] (4) The sheared roll is annealed. First, the furnace temperature is raised to 250°C in 3 hours and held for 5 hours. Then, the furnace temperature is raised to 380°C in 5 hours and held for 8 hours. Then, the furnace temperature is raised to 480°C in 3 hours and held for 6 hours. Then, the furnace temperature is raised to 580°C in 3 hours and held until the temperature of the sheared roll reaches 510°C. Then, the furnace temperature is lowered to 520°C and held for 4 hours. The roll is then removed from the furnace to obtain electronic aluminum foil.

[0096] test:

[0097] 1. During the preparation of electronic aluminum foil in each embodiment and comparative example, samples were taken after cleaning and tested for dyne value using a dyne pen. The test was conducted in accordance with GB / T 14216-2004 "Test Method for Wetting Tension of Plastic Films and Sheets". A standard dyne pen was used to draw lines on the surface of the aluminum foil, and the maximum value of the liquid film without shrinkage was taken as the test result.

[0098] 2. The uniformity of the oxide film of the electronic aluminum foil prepared in each embodiment and comparative example was tested. The thickness of the transverse oxide film was detected by the zero-volt specific capacitance method and the oxide film thickness dispersion was calculated. The calculation methods of oxide film thickness and dispersion are shown in Table 1 below.

[0099] Table 1

[0100]

[0101] 3. The electronic aluminum foils prepared in each embodiment and comparative example were subjected to corrosion foil bending test. Specifically, samples were taken and subjected to four-level corrosion treatment. The operation process is shown in Table 2 below.

[0102] Table 2

[0103]

[0104] After etching and drying, the samples were subjected to SEM surface and cross-sectional analysis, as well as bending tests on the etched foil. The bending was performed according to the SJ / T 11140-2022 standard "Electrode Foil for Aluminum Electrolytic Capacitors". The number of complete bends before breakage was recorded. At the same time, a 520V small sample was formed and the capacitance was tested. The small sample formation and capacitance test were performed according to the SJ / T 11140-2022 standard "Electrode Foil for Aluminum Electrolytic Capacitors".

[0105] 4. Energy consumption tests were conducted on the electronic aluminum foil prepared in each embodiment and comparative example. Specifically, GB / T 2589-2020, "General Rules for Calculating Comprehensive Energy Consumption," was adopted: electricity, compressed air, nitrogen, and other energy-consuming working media were converted to standard coal equivalents as the basis for calculating the comprehensive energy consumption of each process. The comprehensive energy consumption per ton in Example 1 was used as the baseline value (100%). The relative energy consumption calculation formula for the other groups was: Relative Energy Consumption = Comprehensive Energy Consumption per Ton of This Group / Comprehensive Energy Consumption per Ton of Example 1. A percentage > 100% indicates that the energy consumption per unit of aluminum foil in this process is higher than the baseline process of this invention; the larger the value, the more obvious the energy-saving disadvantage. A percentage < 100% indicates that the energy-saving effect is better than the baseline condition. The results are shown in Table 4.

[0106] In Example 1, the measured dyne value reached 62, the average oxide film thickness in the width direction was 2.77 nm, the lateral thickness variation was 4.6%, the capacitance at 520V was 105.4%, the bending time reached 52 times, and the specific capacitance fluctuation was ≤0.8%. The production line speed was stable at 100 m / min, and the energy consumption per ton was set at 100% of the baseline. The SEM surface and cross-section of the etched foil were as follows. Figure 1 and Figure 7 As shown.

[0107] Example 2

[0108] The preparation method of electronic aluminum foil in Example 2 is basically the same as that in Example 1. The difference lies in the setting of the plasma cleaning parameters in Table 3. Specifically, the working gas ternary ratio is Ar 26%, N2 73.5%, and O2 0.5%; the aluminum foil moving speed is 5 m / min, and the power density is 4 W / cm³. 2 The processing time is 12 seconds; the chamber negative pressure is -80 Pa. The ion pulse frequency is 22 Hz.

[0109] Other parameters, conditions, and steps are the same as in Example 1.

[0110] Test results: Dyne value 60, average oxide film thickness 2.81 nm, thickness variation 4.9%, 520V specific capacitance 104.8%, 52 bending cycles, specific capacitance fluctuation ≤0.9%, linear speed 30 m / min, energy consumption per ton 104%, SEM surface and cross-section of the etched foil in Example 2, as shown. Figure 2 and Figure 8 As shown.

[0111] Example 3

[0112] The preparation method of electronic aluminum foil in Example 3 is basically the same as that in Example 1. The difference is that the plasma cleaning parameters in Table 3 are different. Specifically, the working gas has a ternary ratio of Ar 30%, N2 68%, and O2 2%, the aluminum foil moving speed is 150 m / min (high-speed condition), and the power density is 7 W / cm³. 2 The processing time is 4 seconds; the chamber negative pressure is -120 Pa; and the ion pulse frequency is 68 Hz.

[0113] Other parameters, conditions, and steps are the same as in Example 1.

[0114] Test results: Dyne value 62, average oxide film thickness 2.79 nm, thickness variation 4.7%, 520V specific capacitance 105.1%, specific capacitance fluctuation ≤0.8% after 52 bends; limiting linear speed 150 m / min, energy consumption per ton 98%. SEM surface and cross-section of the etched foil in Example 3 are shown below. Figure 3 and Figure 9 As shown.

[0115] Example 4

[0116] The preparation method of electronic aluminum foil in Example 4 is basically the same as that in Example 1. The difference lies in the different ion cleaning parameter settings in Table 3. Specifically, after the foil is rolled, it enters the cleaning process. All sensing, feedback, and integrated units of the cleaning line are turned on, and parameters are corrected in real time every 50ms. The aluminum foil moving speed is increased from 0 to 130m / min in 2 minutes. The initial ternary composition is Ar 26% / N2 73.5% / O2 0.5%, and the ion generator power is 4W / cm. 2 During the acceleration process, the ternary dynamic fluctuation was adjusted to Ar 29% / N2 69.5% / O2 1.5%, and the power was increased from 4W / cm². 2 Fluctuation adjusted to 6.5W / cm 2 The processing time is 4.5s; after the production speed stabilizes, the speed is reduced to 0, and the three-element dynamic adjustment gradually restores the initial conditions. The negative pressure during the cleaning process is uniformly -100Pa, and the frequency of the electrostatic elimination pulse is dynamically adjusted from 22Hz to 60Hz according to the speed.

[0117] Other parameters, conditions, and steps are the same as in Example 1.

[0118] Test results: Samples were tested at acceleration, steady speed, and deceleration speeds. At acceleration, the dyne value was 62, the average oxide film thickness was 2.76 nm, the thickness variation was 4.5%, the 520V specific capacitance was 105.6%, and after 52 bends, the specific capacitance fluctuation was ≤0.7%. At steady speed, the dyne value was 62, the average oxide film thickness was 2.73 nm, the thickness variation was 4.2%, the 520V specific capacitance was 105.4%, and after 52 bends, the specific capacitance fluctuation was ≤0.6%. At deceleration, the dyne value was 61, the average oxide film thickness was 2.77 nm, the thickness variation was 4.7%, the 520V specific capacitance was 105.5%, and after 52 bends, the specific capacitance fluctuation was ≤0.8%. The sample was suitable for speed changes from 0 to 130 m / min, with a single-ton energy consumption of 99%, exhibiting optimal stability under all operating conditions. Example 4 was an adaptive variable operating condition sample, and its steady-state morphology was basically consistent with Example 1.

[0119] Example 5

[0120] The preparation method of electronic aluminum foil in Example 5 is basically the same as that in Example 4. The difference lies in the different settings of the plasma cleaning parameters in Table 3. Specifically, the dynamic adjustment of cleaning parameters is cancelled, and the ternary composition of the working gas is Ar 29% / N2 69.5% / O2 1.5% with a power density of 6.5 W / cm³. 2 The electrostatic discharge pulse frequency is 60Hz.

[0121] Other parameters, conditions, and steps are the same as in Example 4.

[0122] Test Results: Samples were tested at the acceleration, steady-state, and deceleration speeds. At acceleration speed, the dyne value was 68, the average oxide film thickness was 3.46 nm, the thickness variation was 8.5%, the 520V specific capacitance was 95.6%, and after 48 bends, the specific capacitance fluctuation was ≤3.7%. At steady-state speed, the dyne value was 61, the average oxide film thickness was 2.76 nm, the thickness variation was 3.8%, the 520V specific capacitance was 105.6%, and after 52 bends, the specific capacitance fluctuation was ≤0.6%. At deceleration speed, the dyne value was 67, the average oxide film thickness was 3.67 nm, the thickness variation was 9.7%, the 520V specific capacitance was 96.1%, and after 49 bends, the specific capacitance fluctuation was ≤3.8%, with a relative energy consumption per ton of 105%.

[0123] Example 6

[0124] The preparation method of electronic aluminum foil in Example 6 is basically the same as that in Example 1. The difference is that the plasma cleaning parameters in Table 3 are set differently. Specifically, only the gas source drying treatment is reduced, the dew point is controlled at -25℃, and a trace amount of water vapor is introduced into the gas pipeline.

[0125] Other parameters, conditions, and steps are the same as in Example 1.

[0126] Test results: Dyne value 56, average oxide film thickness 2.98nm, thickness variation 7.8%, 520V specific capacitance 98.5%, bending 48 times, specific capacitance fluctuation ≤3.9%, energy consumption per ton 101%; water vapor enters the plasma region and ionizes, causing local oxidation of aluminum foil to form spots, reducing the uniformity of the oxide film and resulting in low capacitance.

[0127] Example 7

[0128] The preparation method of electronic aluminum foil in Example 7 is basically the same as that in Example 1. The difference is that the ion cleaning parameters in Table 3 are set differently. Specifically, only the frequency of the electrostatic eliminator ion bar is fixed at 10Hz.

[0129] Other parameters, conditions, and steps are the same as in Example 1.

[0130] Test results: Dyne value 57, average oxide film thickness 2.88nm, thickness variation 6.1%, 520V specific capacitance 101.9%, bending 51 times, specific capacitance fluctuation ≤2.1%, energy consumption per ton 99%; insufficient electrostatic neutralization capacity, the detached aluminum powder relies on electrostatic secondary adsorption on the foil surface, the cleanliness decreases, and after annealing, it sinters to the surface, causing uneven corrosion.

[0131] Example 8

[0132] The preparation method of electronic aluminum foil in Example 8 is basically the same as that in Example 1. The difference is that the plasma cleaning parameters in Table 3 are set differently. Specifically, only the micro negative pressure suction device below the plasma zone is removed, and there is no real-time extraction of aluminum powder.

[0133] Other parameters, conditions, and steps are the same as in Example 1.

[0134] Test results: Dyne value 54, average oxide film thickness 2.86nm, thickness variation 7.9%, 520V specific capacitance 102.1%, specific capacitance fluctuation ≤2.5% after 50 bends, energy consumption per ton 99%; the aluminum powder after peeling is suspended in the cavity, re-settled and adsorbed on the foil surface, local dust accumulation, which affects local corrosion and porosity after annealing and sintering.

[0135] Comparative Example 1

[0136] The preparation method of electronic aluminum foil in Comparative Example 1 is basically the same as that in Example 1. The difference is that the cleaning process is different. Specifically, the aluminum foil roll is unwound and fed into the cleaning line. Two-stage oil cleaning is used. The cleaning oil is the same type (specifically, light white oil, type D40). The first stage cleaning temperature is set at 50°C, and the second stage rinsing temperature is set at 40°C. During the cleaning and rinsing process, the aluminum foil surface is brushed by a brush roller. After exiting the rinsing tank, the surface is squeezed dry by a squeeze roller. The cleaning speed is 100m / min, and the drying temperature is 140°C to ensure that the foil surface is dry.

[0137] After cleaning, the material roll is left to cool for 24 hours until it cools to below 50°C. Then, it is transferred to a slitting machine for slitting production. The roll is slitted to a width of 500mm. After slitting, it enters the subsequent finished product annealing process to prepare electronic aluminum foil.

[0138] Test results: Dyne value only 38, average oxide film thickness 3.11nm, thickness variation 12.4%, 520V specific capacitance 100.0%, 55 bending cycles, batch specific capacitance fluctuation ≤3.1%; line speed 100m / min, energy consumption per ton 118%, production turnaround 24h. SEM was simultaneously performed to inspect the surface and cross-section of the corroded foil. Figure 4 and Figure 10 As shown, the corrosion pores are uneven in size and the core layer varies greatly in length.

[0139] Comparative Example 2

[0140] The preparation method of electronic aluminum foil in Comparative Example 2 is basically the same as that in Example 1, except that the cleaning process is different. Specifically, after the aluminum foil roll is unwound by the unwinding mechanism, it enters the alkaline washing tank containing alkaline cleaning solution. It is first soaked at 50°C for 8 seconds, and then sprayed for 8 seconds. During the soaking and spraying processes, the surface of the aluminum foil is brushed with a brush roller. After spraying, it is brushed with a brush roller for 2 seconds and then removed from the alkaline washing tank and the surface is squeezed dry. The alkaline cleaning solution in this comparative example consists of: 10 wt.% sodium hydroxide, 6 wt.% sodium silicate, 8 wt.% sodium gluconate, and the remainder is water.

[0141] The aluminum foil was placed in pure water cleaning tank I and pure water cleaning tank II in sequence and sprayed with pure water at a temperature of 50℃. After spraying for 8 seconds in each pure water tank, it was squeezed dry and then dried with hot air in a drying oven at 120℃ for 10 seconds.

[0142] After cleaning, the material roll is left to cool for 24 hours until it cools to below 50°C. Then, it is transferred to a slitting machine for slitting production. The roll is slitted to a width of 500mm. After slitting, it enters the subsequent finished product annealing process to prepare electronic aluminum foil.

[0143] Test results: Dyne value 58, average oxide film thickness 2.87nm, thickness variation 5.3%, 520V specific capacitance 103.2%, 52 bending cycles, specific capacitance fluctuation ≤1.3%; linear speed 100m / min, energy consumption per ton 115%, turnover 24h. SEM was simultaneously performed to inspect the surface and cross-section of the corroded foil. Figure 5 and Figure 11 As shown, the corrosion uniformity is basically the same as that of the embodiments of the present invention, but the energy consumption is high and the wastewater treatment cost is high.

[0144] Comparative Example 3

[0145] The preparation method of electronic aluminum foil in Comparative Example 3 is basically the same as that in Example 2, except that the plasma cleaning parameters in Table 3 are set differently, specifically, the plasma power is fixed at 3W / cm. 2 .

[0146] Other parameters, conditions, and steps are the same as in Example 2.

[0147] Test results: Dyne value 50, average oxide film thickness 3.02nm, thickness variation 9.1%, 520V specific capacitance 99.8%, capacity fluctuation ≤3.0% after 49 bends, energy consumption per ton 93%; oil and aluminum powder were not completely removed, and residual spots remained on the foil surface. The SEM surface and cross-section of the corroded foil in Comparative Example 3 are shown below. Figure 6 and Figure 12 As shown, the surface porosity is uneven and the core layer is irregular.

[0148] Comparative Example 4

[0149] The preparation method of electronic aluminum foil in Comparative Example 4 is basically the same as that in Example 3, except that the plasma cleaning parameters in Table 3 are set differently, specifically, the plasma power is fixed at 8W / cm. 2 .

[0150] Other parameters, conditions, and steps are the same as in Example 3.

[0151] Test results: Dyne value 66, average oxide film thickness 3.35nm, thickness variation 9.8%, 520V specific capacitance 95.6%, bending 48 times, specific capacitance fluctuation ≤1.8%, relative energy consumption per ton 106%. Excessive power caused micro-etching damage to the aluminum foil surface, significantly thickened the oxide film, which in turn affected the corrosion and porosity of the product, resulting in low capacitance and uneven pore length.

[0152] Comparative Example 5

[0153] The preparation method of electronic aluminum foil in Comparative Example 5 is basically the same as that in Example 1. The difference is that the plasma cleaning parameters in Table 3 are set differently. Specifically, only pure argon is introduced into the gas source, and the nitrogen and oxygen gas paths are closed. The other parameters, such as MFC, negative pressure, and static elimination, remain unchanged.

[0154] Other parameters, conditions, and steps are the same as in Example 1.

[0155] Test results: Dyne value 40, average oxide film thickness 3.18nm, thickness variation 11.5%, 520V specific capacitance 90.5%, bending 48 times, specific capacitance fluctuation ≤4.8%, relative energy consumption per ton 98%, no oxygen to decompose long-chain rolling oil, no nitrogen gas curtain, aluminum foil continuously oxidizes during cleaning, and oil residue is serious.

[0156] Comparative Example 6

[0157] The preparation method of electronic aluminum foil in Comparative Example 6 is basically the same as that in Example 1. The difference is that the ion cleaning parameters in Table 3 are set differently. Specifically, only Ar 98% + O2 2% mixed gas is introduced, and the nitrogen supply is completely turned off.

[0158] Other parameters, conditions, and steps are the same as in Example 1.

[0159] Test results: Dyne value 60, average oxide film thickness 3.15nm, thickness variation 10.8%, 520V specific capacitance 101.1%, bending 48 times, specific capacitance fluctuation ≤3.8%, relative energy consumption per ton 98%. The addition of oxygen supply improved the dyne value, but the lack of nitrogen isolation protective gas curtain caused the aluminum foil in the plasma zone to directly contact the air and undergo secondary oxidation, resulting in a significant deterioration in the uniformity of the oxide film, which in turn caused the uniformity of the pores to change and the core layer uniformity to decrease.

[0160] Comparative Example 7

[0161] The preparation method of electronic aluminum foil in Comparative Example 7 is basically the same as that in Example 1. The difference is that the ion cleaning parameters in Table 3 are set differently. Specifically, only Ar 28% + N2 72% is introduced, and the oxygen supply is cut off.

[0162] Other parameters, conditions, and steps are the same as in Example 1.

[0163] Test results: Dyne value 47, average oxide film thickness 3.09nm, thickness variation 12.1%, 520V specific capacitance 98.3%, bending 49 times, specific capacitance fluctuation ≤4.5%, relative energy consumption per ton 99%, no oxygen involved in oxidation chain scission, rolling oil cannot be completely decomposed, a large amount of organic residue annealing forms carbon spots, and in subsequent corrosion tests, the surface porosity is increased and the pore length is uneven, resulting in lower capacity and bending performance.

[0164] Comparative Example 8

[0165] The preparation method of electronic aluminum foil in Comparative Example 8 is basically the same as that in Example 1. The difference is that the plasma cleaning parameters in Table 3 are different. Specifically, only the oxygen volume ratio is adjusted to 5%, the ternary ratio is Ar 28%, N2 67%, and O2 5%; the gas source dew point, power, and production line speed remain unchanged, and the product is slit and annealed after cleaning.

[0166] Other parameters, conditions, and steps are the same as in Example 1.

[0167] Test results: Dyne value 66, average oxide film thickness 3.63nm, thickness variation 9.2%, 520V specific capacitance 90.9%, 49 bends, specific capacitance fluctuation ≤4.9%, relative energy consumption per ton 99%. Excess oxygen accelerates the decomposition of foil rolling oil under plasma field, and at the same time violently oxidizes the aluminum matrix, causing the foil surface to turn white and exhibit color difference. After annealing, the oxide film thickens, affecting subsequent corrosion and pitting, thus causing low capacitance.

[0168] The above comparison shows that low Ar results in poor aluminum powder peeling, while high Ar results in weak oil decomposition; insufficient O2 results in residual carbon spots, while excessive O2 results in corrosion of the aluminum substrate; low N2 results in foil oxidation, while excessive N2 results in plasma energy dilution. As a result, the dyne value, oxide film dispersion, and specific volume index are all significantly worse than those of Example 1.

[0169] Table 3

[0170]

[0171] Table 4

[0172]

[0173] As can be seen from the examples and comparative examples, the electronic aluminum foil products produced using this application have a thinner oxide film thickness and a smaller oxide film thickness variation in the width direction after annealing at a temperature above 500°C. This indicates that the aluminum foil surface is more uniform and more conducive to subsequent corrosion. After electrochemical corrosion, under basically the same bending conditions, the capacity of the present invention is higher. At the same time, in terms of energy consumption, the present invention has the lowest energy consumption while improving product performance and stability.

[0174] from Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 By comparing SEM images of the corroded surfaces, Figure 1 , Figure 2 and Figure 3 After corrosion, the distribution of corrosion pits is more uniform, and the degradation trend of the microstructure of the corrosion surface and cross-section of each group is consistent, especially... Figure 1 This distribution exhibits the best performance, maximizing the specific surface area and thus improving the product's specific capacitance. Figure 4 , Figure 5 and Figure 6 The comparative products, among which Figure 4 and Figure 6Poor distribution is mainly due to incomplete surface cleaning, resulting in poor surface uniformity. During subsequent corrosion, simultaneous corrosion cannot be achieved, causing uneven local current distribution and leading to this phenomenon. Poor uniformity of pore size and small specific surface area are also one of the reasons for the relatively low capacity.

[0175] from Figure 7 , Figure 8 , Figure 9 , Figure 10 , Figure 11 and Figure 12 Comparing the SEM images of the etched cross sections, the electronic aluminum foil products produced by this invention exhibit good core layer uniformity after etching, further demonstrating high surface cleanliness and consistency. The uniform core layer shows high corrosion consistency, which significantly improves the product's capacity and strength. Figure 10 and Figure 12 The occurrence of core layer pore penetration, with pores of varying lengths, is detrimental to both capacity improvement and product strength consistency.

[0176] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0177] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A method for preparing electronic aluminum foil, characterized in that, Includes the following steps: In the working gas, the power density is 4 W / cm³ 2 ~7 W / cm 2 Under these conditions, aluminum foil rolls are subjected to plasma cleaning. The working gas, by volume percentage, comprises the following components: Ar 26%~30%, N2 68%~73.5%, and O2 0.5%~2%; and The aluminum foil after plasma cleaning is annealed to prepare electronic aluminum foil.

2. The method for preparing electronic aluminum foil as described in claim 1, characterized in that, The working gas comprises the following components by volume percentage: Ar 28%~30%, N2 68%~70.8% and O2 1.2%~2%.

3. The method for preparing electronic aluminum foil as described in claim 1, characterized in that, The method for preparing the electronic aluminum foil satisfies one or more of the following conditions: (1) The thickness of the aluminum foil rolled product is 80μm~130μm; (2) The dew point of the working gas source is less than or equal to -25℃; (3) The plasma cleaning time is 4s~12s; (4) The annealing temperature is 250℃~580℃ and the time is 25h~38h.

4. The method for preparing electronic aluminum foil according to any one of claims 1 to 3, characterized in that, During the plasma cleaning process of aluminum foil rolls, the moving speed of the aluminum foil rolls is less than or equal to 150 m / min. As the moving speed of the aluminum foil rolls increases from 0 to 150 m / min, the composition and power density of the working gas are adjusted in real time.

5. The method for preparing electronic aluminum foil as described in claim 4, characterized in that, As the moving speed of the aluminum foil rolled product increases from 0 to 130 m / min, the power density increases from 4 W / cm². 2 Adjusted to 6.5W / cm 2 The volume ratio of Ar, N2 and O2 was adjusted from 26:73.5:0.5 to 29:69.5:1.

5.

6. The method for preparing electronic aluminum foil according to any one of claims 1 to 3 and 5, characterized in that, The method for preparing the electronic aluminum foil satisfies one or more of the following conditions: (1) Before the step of annealing the aluminum foil after plasma cleaning, the aluminum foil after plasma cleaning is further subjected to pulse treatment and shearing treatment in sequence. (2) The process of plasma cleaning of aluminum foil rolled products also includes negative pressure suction of aluminum foil to remove the detached aluminum powder particles.

7. The method for preparing electronic aluminum foil as described in claim 6, characterized in that, The method for preparing the electronic aluminum foil satisfies one or more of the following conditions: (1) The frequency of pulse processing is 10Hz~68Hz; (2) The pressure of negative pressure suction is -80 Pa to -120 Pa.

8. The method for preparing electronic aluminum foil according to any one of claims 1 to 3, 5, and 7, characterized in that, Before the plasma cleaning step of the aluminum foil roll product, the process also includes a surface pretreatment step of the aluminum foil roll product to remove free impurities on the foil surface.

9. An electronic aluminum foil, characterized in that, The electronic aluminum foil is prepared by the method described in any one of claims 1 to 8.

10. A capacitor, characterized in that, It includes an anode, a cathode, a diaphragm, and an electrolyte, wherein the anode is prepared using an electronic aluminum foil prepared by the method described in any one of claims 1 to 8 or the electronic aluminum foil described in claim 9.